PNEUMATIC ACTUATION OF LASER BEARING ENGRAVING STATION (Nonconventional Technologies Review, 2021)
The paper presents the design and construction of a laser bearing inscription station. The station is designed in a SolidWorks program, each mechanical component is draw in a Part file and late all components are assembled into a final drawing. The execution drawing of each element is thus transmitted for processing. What is important for carrying out the project, the pneumatic control elements are also generated in SolidWorks too, by the manufacturing company and thus their design can be used to complete the assembly. An important thing in the work was the simulation of the pneumatic circuit which allowed the choice of the components according to the program. The practical manufacturing of the project also required the realization of the electrical installation. The company makes specialized equipment and prototypes for automotive companies. One of the novelties was the use of the filter during the laser inscription to improve the ergonomics of the work environment.
Keywords: bearings; laser engraving; pneumatic; filter; electric